Pyrite (FeS2)-supported ultrafiltration system for removal of mercury (II) from water - Dong Suk Han (1748989) (2022)
This study investigated the Hg(II) removal efficiencies of the reactive adsorbent membrane (RAM) hybrid filtration process, a removal process that produces stable final residuals. The reaction mechanism between Hg(II) and pyrite and the rejection of the solids over time were characterized with respect to flux decline, pH change, and Hg and Fe concentration in permeate water. Effects of the presence of anions (Cl−, SO42−, NO3−) or humic acid (HA) on the rejection of the Hg(II)-contacted pyrite were studied. The presence of both HA and Hg(II) increased the rate of flux decline due to the formation of irreversible gel-like compact cake layers as shown in the experimental data and modeling related to the flux decline and the SEM images. Stability experiments of the final residuals retained on the membrane using a thiosulfate solution (Na2S2O3) show that the Hg(II)-laden solids were very stable due to little or no detection of Hg(II) in the permeate water. Experiment on the possibility of continuously removing Hg(II) by reusing the Hg/pyrite-laden membrane shows that almost all Hg(II) was adsorbed onto the pyrite surface regardless of the presence of salts or HA, and the Hg(II)-contacted pyrite residuals were completely rejected by the DE/UF system. Therefore, a membrane filter containing pyrite-Hg(II) could provide another reactive cake layer capable of further removal of Hg(II) without post-chemical treatment for reuse. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s42247-021-00282-7